Measuring Rogers' conception of personality development: validation of the Strathclyde Inventory-French version. (3rd April 2018) - Zech, Emmanuelle; Brison, Céline; Elliott, Robert; Rodgers, Brian; Cornelius-White, Jeffrey H. D.
ABSTRACT: The Strathclyde Inventory (SI) was created as an outcome measure to go beyond symptom intensity. It is designed to assess personality development such as congruent and flexible functioning from a person-centered perspective. The present study validated the data obtained from the 22-item French version of the SI collected in eight samples, including student groups and patients from four different hospital settings. This study describes the psychometric properties of the Strathclyde Inventory-French version. Results indicated high internal consistency and test–retest reliability. A single general Congruence vs. Incongruence factor structure with two subfactors was found. The scale scores indicate sensitivity to the effects of two types of experiential trainings among university students and in an alcohol withdrawal program for hospitalized patients but did not show change in the absence of experiential training and in treatment as usual conditions among cancer and psychiatric patients. Construct validity was confirmed using correlations with data from trait, behavioral and symptom measures. The results indicated that the scale is well designed to assess the process of personality development in training helping professionals and therapy process-outcome studies.